Reexamination of Yuknessia from the Cambrian of China and first report of Fuxianospira from North America. (9th May 2016) - LoDuca, Steven T.; Wu, Mengyin; Zhao, Yuanlong; Xiao, Shuhai; Schiffbauer, James D.; Caron, Jean-Bernard; Babcock, Loren E.
Abstract: Yuknessia Walcott, 1919 recently was transferred from the green algae to the Phylum Hemichordata on the basis of new details observed for the type species, Y . simplex, from the Burgess Shale Formation (Cambrian Stage 5) of British Columbia. This has prompted reexamination of material attributed to Yuknessia from various Cambrian localities in South China. Findings preclude both a Yuknessia and a hemichordate affinity for all of the Chinese study material, and most of this material is formally transferred to Fuxianospira Chen and Zhou, 1997, a taxon common in the Chengjiang biota. Comparable material from the Cambrian Marjum, Wheeler, and Burgess Shale formations of North America is also assigned to Fuxianospira, and this reassignment expands both the paleogeographic and stratigraphic range of this taxon. All aspects of the study specimens, including details obtained from scanning electron microscopy, are consistent with an algal affinity, as proposed in the original descriptions of the Chinese material.